Avaliação dos parâmetros agronômicos da cultura do trigo na fase de perfilhamento com aeronave remotamente pilotada - ARP - Lavezzo, Thaina Sanguanini (2021)
Remote sensing applications using remotely piloted aircraft (ARP) in agriculture have proven to be an effective and efficient way to obtain information in the field. In this study, the use of images collected by an ARP using the camera embedded in the equipment and free-use software such as QGIS, Drone Deploy and Microsoft Excel in the evaluation of agronomic parameters of wheat crop in the tillering phase in 12 different genotypes was evaluated . For evaluation, VDVI and ExG vegetation indices were used, in view of their applicability and popularization in other cultures. From the images collected with the ARP, digital processing was performed and maps were made for evaluating the genotypes from the indexes. Through the generated data, Pearson's simple statistical correlation was performed with the characters of leaf areanindex, dry mass concentration and grain yield. It was possible to diagnose the unfeasibility of the methodology for evaluating the agronomic characters of the crop in the tillering phase. It is concluded that the indices used showed a result of low applicability for the crop in the initial phase of vegetative development and that the ARP and free platforms are viable for collecting information, easy to operate, allowing the agronomist and rural producer to monitor the culture and make decisions with greater assertiveness, causing less impact and at reduced cost.